2014
DOI: 10.1002/eat.22251
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training enhances muscular performance in patients with anorexia nervosa: A randomized controlled trial

Abstract: A high-intensity resistance training program adapted to the recommendations for adolescents in AN-R patients was effective and safe, improving muscular strength in the whole body and the ability to perform daily tasks. However, long-term maintenance of gains seems to be linked to the continuance of training or the use of a maintenance program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 40 publications
2
52
1
1
Order By: Relevance
“…Patients with AN also demonstrated improved number of push-ups and hand grip strength upon treatment discharge, despite significant increases in BMI. Increased strength in AN is well supported by previous research (del Valle et al, 2010;Fernandez-del-Valle et al, 2014), but the concurrent increase in BMI while improving strength in AN is a relatively new finding. This is especially noteworthy given that complications of AN, such as endocrine and cardiorespiratory issues, gastrointestinal problems, and physical weakness can contribute to the deterioration of power and strength (Academy of Eating Disorders, n.d.).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Patients with AN also demonstrated improved number of push-ups and hand grip strength upon treatment discharge, despite significant increases in BMI. Increased strength in AN is well supported by previous research (del Valle et al, 2010;Fernandez-del-Valle et al, 2014), but the concurrent increase in BMI while improving strength in AN is a relatively new finding. This is especially noteworthy given that complications of AN, such as endocrine and cardiorespiratory issues, gastrointestinal problems, and physical weakness can contribute to the deterioration of power and strength (Academy of Eating Disorders, n.d.).…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, Moola, Gairdner, and Amara (2013) found that nutritionally supported exercise lessens food preoccupation, enhances treatment compliance, increases bone density, and improves quality of life in medically stable inpatients with AN. Exercise has also been shown to increase muscle strength in patients with AN, though no significant increases in BMI were found in these studies (del Valle et al, 2010;Fernandez-del-Valle et al, 2014). Additional measures of strength and BMI are needed to investigate the effectiveness of exercise within intensive ED treatment centers for all patients, particularly athlete patients.…”
Section: Exercise In Intensive Ed Treatment Centersmentioning
confidence: 85%
“…Indeed, the positive association between exercising at high intensity and a better nutritional status (higher BMI and FFMI values) is in line with the idea of including adapted physical activity sessions in AN treatment (Ng et al, ). Moderated under the appropriate conditions (adapted to the food intake and energy expenditure of the patient and taking into account bone mineral density and cardiac function (American Psychiatric Association, ), supervised exercise interventions integrated in AN inpatient treatment appeared to be safe (Fernandez‐del‐Valle et al, ; Hausenblas et al, ; Ng et al, ; Vancampfort et al, ; Zunker et al, ), preserved bone mineral density (Achamrah et al, ), helped manage mood and anxiety (Achamrah et al, ), and were associated with a positive outcome and a significant decrease in patients' concerns about body weight and shape (Zunker et al, ). These interventions may also increase the compliance with outpatient treatment (Thien, Thomas, Markin, & Birmingham, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a growing body of evidence suggesting that closely monitored, nutritionally supported exercise is safe and may convey multiple benefits in individuals with ED. For example, previous research has demonstrated an effect for exercise to decrease obligatory exercise attitudes and behaviors (7), reduce drive for thinness, bulimic symptoms, decrease body dissatisfaction (10,41), facilitate weight gain in anorexia nervosa(AN) (7,8), increase strength (17), reverse cardiac abnormalities in severe AN(26), and improve quality of life (9,11,14,15). This area of research suggests substantial help may be possible from delivering an appropriate exercise treatment protocol as part of an ED treatment.…”
Section: Introductionmentioning
confidence: 99%